Early p38 Activation Regulated by MKP-1 Is Determinant for High Levels of IL-10 Expression Through TLR2 Activation - Francisco, Sara; Arranz, Alicia; Merino, Javier; Punzón, Carmen; Perona, Rosario; Fresno, Manuel (Frontiers in Immunology, 2021)
Toll-like receptors (TLRs) play a crucial role in the recognition of pathogen-derived components as a first line of defense against infections. It has been suggested that depending on the nature of the pathogens, TLRs activation induce a distinct cytokine profile that may contribute to the polarization of the acquired immune response. Here, we investigated the early MAPK signaling activation via TLR4 and TLR2 receptors and its impact in differential cytokine profile by macrophages. We found that TLR2 ligands activated MAPKs p38 and ERK earlier compared to the TLR4 ligand LPS in macrophages. Higher IL-10 /IL-12 and IL-10/TNF-α ratios were also observed at later time points in response to TLR2 ligands compared to LPS. The results also indicate an earlier activation of the phosphatase MKP-1 and that MKP-1 KO macrophages show a prolongation in p38 phosphorylation in response to TLR2 stimulation. Furthermore, p38 is critical for IL-10 expression in response to TLR2 ligands, which triggers the macrophage change to a M2 and regulatory phenotype in contrast to the M1 phenotype induced by TLR4 activation. Therefore, the early TLR2-mediated p38 induction contributes for the high IL-10 production, likely as a virulence strategy to suppress host Th1 response against certain types of pathogens.